Unfurling a case of encephalitis with Acanthamoeba after a near-drowning event - Debarup Das; Kuntal Biswas; Kokila Banerjee; Bhaswar Bhattacharya; Arijit Roy; Sumeeta Khurana; Atanu Biswas (Rare)
Acanthamoeba is a free-living ameba which is known to cause keratitis, encephalitis, and disseminated infections in human beings. Granulomatous amebic encephalitis (GAE) is classically seen in immunocompromised hosts. Here the authors present a patient with meningoencephalitis following accidental near drowning in a pond from eastern India which subsequently proved to be a case of Acanthamoeba associated encephalitis but presented acutely contrary to known literature. Acanthamoeba was seen in direct wet mount examination of Cerebrospinal fluid (CSF) samples and subsequently isolated by culture and detected by PCR (polymerase chain reaction) test. Magnetic Resonance imaging (MRI) showed multiple hemorrhagic infarcts with leptomeningeal enhancements. The unusual acute presentation by this rare infectious agent, CSF showing neutrophilic pleocytosis and grave prognosis in an apparently immunocompetent host make this case unique and noteworthy. Acanthamoeba related meningoencephalitis can be fatal if it’s not diagnosed early. Acanthamoeba as an etiological agent must be suspected even in immunocompetent hosts when there is a history of freshwater bathing or drowning.